Potential of Soundproof Wallpaper Based on Indigenous Materials - Hidayati, Rahmanisa Nur; Wulan, Dewi Candra; Fauziah, Amalia; Rahayu, Ngesti; Subali, Bambang (Jurnal Scientia Indonesia, 2015)
Noise exposure can occur at any time and interfere with a person's psychological and biological condition. Alternative materials from banana midrib and soybean dregs can be used as sound absorbers based on their characteristics and abundance. This research aims to analyze the optimal composition for sound-absorbing composite materials from banana midrib and soybean dregs and the effect of adding a layer of varnish to its absorption capacity. The method includes the manufacture of the sample, the impedance tube, the box acoustic approach, and the CCD test. The drying process of banana midrib is divided into two types, namely those that are dried in the sun and oven with the banana midrib having gone through a 5% NaOH immersion process before drying. The application of varnish on the sample used the cold spray technique so the layer is not thick and provides durability and resistance to the sample. The impedance tube was carried out to analyze the value of the sound absorption coefficient of the sample at several frequencies which were then averaged. After being tested with the box acoustic approach, the sample has the ability to reduce sound when applied to the walls of the room with an average percentage decrease of 10.84%. Through the CCD test, it is known that the size and number of pores distribution affects the sound absorption capacity. Banana midrib and soybean dregs can be used as an alternative to sound absorbers with the average value meeting the ISO 11654 standard, which is 0.15.